2009
DOI: 10.1021/la8042796
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Esters of Arjunolic Acid into Fibrous Networks and the Properties of their Organogels

Abstract: Nine esters of a naturally occurring triterpenoid, arjunolic acid (from Terminalia arjuna), with alkyl chains have been synthesized, and their self-assembly has been studied in organic liquids. All of the esters examined were found to be excellent gelators. No birefringence was detected in optical micrographs of the transparent toluene gels with 5% (w/w) ethyl arjunolate or 5% (w/w) p-nitrobenzyl arjunolate as the gelator, but a spherulitic-type pattern was seen for a gel of 1.2% (w/w) p-nitrobenzyl arjunolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 38 publications
0
56
0
1
Order By: Relevance
“…The self-assembly behavior of 7 was studied in different mixed solvents. The primary results showed that 7 could form weak organogel in THF-methanol (V∶ V=3∶1) with the MGC of 2.3 g/100 cm 3 (MGC, minimum gelator concentration at which gelation was observed to restrict the flow of the medium 28 ) and the T gel =36 ℃ (T gel , the required temperature for the organogel to collapse, was determined by the dropping ball method at MGC 33 ) (Figure 2a). To gain visual insight into the aggregation mode of this weak gel, scanning electron microscopy (SEM) was used to investigate the gel structure (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-assembly behavior of 7 was studied in different mixed solvents. The primary results showed that 7 could form weak organogel in THF-methanol (V∶ V=3∶1) with the MGC of 2.3 g/100 cm 3 (MGC, minimum gelator concentration at which gelation was observed to restrict the flow of the medium 28 ) and the T gel =36 ℃ (T gel , the required temperature for the organogel to collapse, was determined by the dropping ball method at MGC 33 ) (Figure 2a). To gain visual insight into the aggregation mode of this weak gel, scanning electron microscopy (SEM) was used to investigate the gel structure (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20][21] Despite of chiral rigid skeleton, relative low-toxicity and biocompatibility, there is few reports about triterpenoids as the scaffolds in supramolecular and recognition chemistry. [22][23][24][25][26][27][28] To continue our previous work 23,24,29,30 a new kind fan-shaped C 3 molecule with three GA units ( Figure 1) was synthesized and the self-assembly properties were studied.…”
Section: Introductionmentioning
confidence: 98%
“…[5] With similar structural properties as the biogenic homologue of steroids, triterpenoids (18β-glycyrrhetinic acid, oleanolic acid) have also started to emerge in recognition and assembly systems, thus attracting more and more attention from organic and material scientists. [6][7][8] Among the synthesized macrocyclic steroidal dimers the compounds with good inverse recognition properties, [9] as well as cytotoxic hormone receptor modulating activities [10] were obtained. Glycyrrhetinic acidtweezer receptors with excellent selectivity and affinity for Hg 2+ ion, [11] and stable cyclic dimer based on oleanolic acid with remarkable binding ability to F -ion [7] were reported.…”
Section: Introductionmentioning
confidence: 99%
“…The solvent was evaporated, the residue was subjected to chromatography on silica gel (eluent chloroform-methanol, 100:2) to isolate 0.394 g (53 %) of compound 17 and 0.220 g (30 %) of dimeric compound 18. (1S,4aR,5S,8aR) (6). 1-azido-2-(2-azidoethoxy)ethane 5 (0.17 g, 1.07 mmol) was added to a mixture of compound 11 (0.50 g, 1.07 mmol) in dichloromethane (107 mL) and solutions of CuSO 4 •5H 2 O (0.11 g, 0.43 mmol) in H 2 O (0.5 mL) and sodium ascorbate (0.21 g, 1.07 mmol) in H 2 O (0.5 mL) with stirring.…”
Section: Introductionmentioning
confidence: 99%
“…Organogels are generating great interest and expectation in a wide spectrum of applications such as medical and pharmaceutical [1][2][3][4], development of new materials with specific optical and mechanical properties [5][6][7], matrixes for food systems [8,9], art conservation [10,11], etc. The term organogel refers to a variety of soft materials, from viscoelastic liquid-like to solid-like, comprised of an organic liquid and some molecules, i.e., organogelators, which are able to produce self-assembling and structure the organic medium [12].…”
Section: Introductionmentioning
confidence: 99%